Uncertain Times Equals Opportunities - Jeri W Dunkin (Rural Nurse Organization; Binghamton University, 2008)
As nurses we must be alert to opportunities to assist our communities as we move through these difficult times around the world. There will certainly be an impact on the health of all people as the economic dynamics of the current world wide recession evolves before us. Nurses are problem solvers who are not afraid to use innovative solutions. Rural nurses, particularly, have done this for a long time as the rural areas are always resource poor and thus the use "non-traditional" approaches are not new. Thus, we must be ready for the opportunities that will come to us individually and as rural nurse and members of the nursing professions as the economies of regions and even nations struggle to come to balance. The American Academy of Nursing has released a video that talks about the role of nurse and nursing leadership in health care reform. It addresses the need to have nursing actively participate in any health policy discussions. Nursing has repeatedly demonstrated models that are efficient and effective in improving patient outcomes while reducing the cost of health care. The video can be viewed at http://www.youtube.com/user/AANRaisetheVoice. Let us be ready...